Experience is more important than technology in paediatric post-tonsillectomy bleeding. (10th April 2017) - Hinton-Bayre, A D; Noonan, K; Ling, S; Vijayasekaran, S
Abstract: Background: Paediatric tonsillectomy is a common procedure and one of the first skills acquired by surgical trainees. Post-tonsillectomy bleeding is one of the most significant complications. This study examined post-tonsillectomy bleed rates associated with technology and level of surgical experience. Methods: Data were collected on all tonsillectomies performed by surgical consultants ( n = 6) and trainees ( n = 10) at affiliated hospitals over a nine-month period. Hospital records were audited for post-tonsillectomy bleeding re-admissions and returns to the operating theatre. Results: A total of 1396 tonsillectomies were performed (279 by trainees, 1117 by consultant surgeons). Primary post-tonsillectomy bleed rates were equivalent between trainees and consultants. Secondary bleed rates were significantly greater for trainees (10.0 per cent) compared to consultants (3.3 per cent), as were return to operating theatre rates (2.5 per cent vs 0.7 per cent). Amongst consultants, technology used was not associated with differences in secondary post-tonsillectomy bleeding and returns to the operating theatre. Conclusion: Our data suggest that experience of the surgeon may have greater bearing on post-tonsillectomy bleed rates than the technology used.